Catastrophic volcanism and its implication for agriculture in the Maya Lowlands. (February 2016) - Tankersley, Kenneth Barnett; Dunning, Nicholas P.; Scarborough, Vernon; Huff, Warren D.; Lentz, David L.; Carr, Christopher
Abstract: Powder X-ray diffraction, high-magnification microscopy, and whole rock X-ray fluorescence spectrometry analyses of sediment samples collected from an ancient Maya reservoir at Tikal, Guatemala in 2009 demonstrated conclusively that volcanic ash was repeatedly deposited on the site. To test the hypothesis that volcanic ash was a major contributor of new parent material to soils in the southern Yucatan Peninsula we used these same techniques to analyze samples taken from several natural depressions (bajos) in the region. Our findings clearly indicate that volcanic ash is a major constituent of regional soils. Hence, explosive volcanism was a critical factor in the development and maintenance of ancient Maya urban centers by renewing agricultural soils. These centers were typically low-density "garden cities" largely dependent on their immediate environs for agricultural production. For these cities to flourish in a difficult environment a flux of volcanic material occurring within an optimal window was critical. Regional wind patterns and rainfall are seasonal, linked to the annual shift in the Intertropical Convergence Zone (ITCZ). During the wet season, the ITCZ sits over the Yucatan Peninsula with Trade Winds and Easterly Waves predominating and blocking ash fall from reaching the Maya Lowlands from the volcanic arc to the south. During the dry season, the southward shift of the ITCZ allows westerly and southerly winds to bring erupted ash over the region. However, ash fall occurring during the dry season also posed a risk for ancient Maya, who were dependent on capturing and storing rainwater to meet their water needs because of the problem of reservoir fouling. Intermittent periods of increased aridity amplified drought frequency and severity, which likely contributed to periods of disruption in the course of Maya prehistory. Highlights: A significant portion of the soil across the Maya Lowlands originated as weathered volcanic ash. Volcanic ash fall provided a mechanism for renewing soil fertility and provided essential raw material for ceramic production. Volcanic ash fall in the Maya Lowland originated from volcanoes in El Salvador, Guatemala, and Mexico.